“We are living in dark times”: State Intervention in Mexico City Communication Media (Andamios, Revista de Investigación Social, 2025)
Through 42 in-depth interviews and drawing on Hallin and Mancini, the article explores the perceptions of journalists from Mexico City about state intervention in the media and their work in the framework of the Fourth Transformation. According to the findings, we can see this interference through unequal relatedness between the State and the media; the government and its institutions are indispensable sources, but access to them is complicated; the dependence on official advertising continues, which can lead to favorable coverage; the daily agenda is positioned through Presidency communication exercises, while critical journalists face at censorship, and finally, we can observe a radicalization in criticism towards journalists.
Keywords: State Intervention; media communication; journalists; Fourth Transformation; Mexico City